Композиционный материал для коллекторов электрических машин - Бекишев Р. Ф. Рудольф Фридрихович; Качин С. И. Сергей Ильич; Константинов Г. Г. Геннадий Григорьевич; франк В. А. Владимир Андреевич
опубл. 15.02.83